The influence of alkaline treatment on thermal stability of flax fibres - J Chaishome; S Rattanapaskorn (My University, 2017)
The paper pursued the hypothesis that alkaline treatment removed hemicellulose and pectin from the flax fibres, the fibre thermal stability will be improved. The use of plant fibres as reinforcement in thermoplastic composites comes with the detrimental effect of thermal degradation on the tensile performance of fibres and composites, particularly during long consolidation times at high temperature. SEM was used to observe the treated fibre surface. The micrographs show that the treatment with a higher concentration of NaOH solution results in a more obviously rough fibre surface. Moreover, FTIR and TGA were used to examine the chemical decomposition and thermal stability, respectively. The spectra of treated materials indicate that both hemicellulose and pectin were dissolved from the fibre surface following treatment. Finally, TGA results revealed that the loss of mass belonging to hemicellulose and pectin in treated fibres results in a shift of the main degradation temperature to higher temperature.
Keywords: Hemicellulose; Pectin; Thermal Stability; Thermogravimetric analysis; Degradation; Thermal Treatment; Natural Fiber Reinforced Composites